Greek Philosophy: The Classic View of Education - Rahmawati, Zuli Dwi; Asadori, Asadori; Haris, Abd.; Mansur, Rosichin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2023)
Education began with the classical view of ancient Greek philosophy regarding logical truth, in the medieval period there was a restriction on freedom of thought by the church on the grounds that truth could not be produced by reason as happened in the ancient Greek period, after that came the modern period called the renaissance , namely the school of thought. rationalism which prioritizes reason as a source of knowledge. From knowledge that continues to develop, new ideas and knowledge emerge that make the world of education activities increasingly complex. This history-based educational theory research uses a qualitative approach with a type of bibliographic research so as to present accurate historical facts in accordance with theory from various historical experts' points of view. The science developed in western education is philosophy which is formed as a reference for their thinking, which will give rise to thoughts characterized by materialism, idealism, secularism and rationalism.